Intra- and Extracellular Pillars of a Unifying Framework for Homeostatic Plasticity: A Crosstalk Between Metabotropic Receptors and Extracellular Matrix - Cingolani, Lorenzo A.; Vitale, Carmela; Dityatev, Alexander (Frontiers in Cellular Neuroscience, 2019)
In the face of chronic changes in incoming sensory inputs, neuronal networks are capable of maintaining stable conditions of electrical activity over prolonged periods of time by adjusting synaptic strength, to amplify or dampen incoming inputs (homeostatic synaptic plasticity; HSP), or by altering the intrinsic excitability of individual neurons (homeostatic intrinsic plasticity, HIP). Emerging evidence suggests a synergistic interplay between extracellular matrix (ECM) and metabotropic receptors in both forms of homeostatic plasticity. Activation of dopaminergic, serotonergic or glutamate metabotropic receptors stimulates intracellular signaling through CaMKII, PKA, PKC and IP3Rs, and induces changes in expression of ECM molecules and proteolysis of both ECM molecules (lecticans) and ECM receptors (NPR, CD44). The resulting remodeling of perisynaptic and synaptic ECM provides permissive conditions for HSP and plays an instructive role by recruiting additional signaling cascades, such as those through mGluRs and integrins. The superimposition of all these signaling events determines intracellular and diffusional trafficking of ionotropic glutamate receptors, resulting in HSP and modulation of conditions for inducing Hebbian synaptic plasticity (i.e. metaplasticity). It also controls cell-surface delivery and activity of voltage- and Ca2+-gated ion channels, resulting in HIP. These mechanisms may modify epileptogenesis and become a target for therapeutic interventions.